On the fast modeling of species transport in fluidized beds using recurrence computational fluid dynamics. Issue 5 (10th February 2020) - Dabbagh, Firas; Pirker, Stefan; Schneiderbauer, Simon
Abstract: Due to variety of scale dynamics evolved in gas–solid flows, most of its numerical description is limited to expensive short durations. This has made the slow processes therein, such as the chemical species conversion, to be out of an appropriate reach. In this work, an application of the transport‐based recurrence computational fluid dynamics (CFD) has been introduced for the fast modeling of passive scalar transport, which is considered as species conversion and heat transfer in fluidized beds. The methodology discloses the recurrent dynamics during a short‐term full CFD simulation as Lagrangian shift operations upon which a passive scalar can infinitely be traced. Apart from convecting, a proper approach based on the turbulent kinetic energy of tracked dynamics is introduced for modeling the physical diffusion of the scalar transported. Our outcomes have revealed a subtle chasing to the full CFD species simulation with a speed‐up up to 1, 600.